2009
DOI: 10.1530/rep-09-0023
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone induction of prostaglandin-endoperoxide synthase 2 expression and prostaglandin F2α production in hamster Leydig cells

Abstract: We have previously observed expression of prostaglandin-endoperoxide synthase 2 (PTGS2), the key enzyme in the biosynthesis of prostaglandins (PGs), in reproductively active Syrian hamster Leydig cells, and reported an inhibitory role of PGF 2a on hamster testicular steroidogenesis. In this study, we further investigated PTGS2 expression in hamster Leydig cells during sexual development and photoperiodic gonadal regression. Since PTGS2 is mostly expressed in pubertal and reproductively active adult hamsters wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 67 publications
0
37
0
Order By: Relevance
“…On the other hand, in adult hamsters exposed to a short-day photoperiod and also in prepubertal hamsters, testicular COX2 is barely detected, coinciding with low serum concentrations of LH, PRL, and androgens (Frungieri et al 2006, Matzkin et al 2009, 2012b. These results suggest that some hormones (LH, PRL, and/or androgens) could be involved in the regulation of testicular COX2 expression and PG production.…”
Section: R171mentioning
confidence: 90%
See 3 more Smart Citations
“…On the other hand, in adult hamsters exposed to a short-day photoperiod and also in prepubertal hamsters, testicular COX2 is barely detected, coinciding with low serum concentrations of LH, PRL, and androgens (Frungieri et al 2006, Matzkin et al 2009, 2012b. These results suggest that some hormones (LH, PRL, and/or androgens) could be involved in the regulation of testicular COX2 expression and PG production.…”
Section: R171mentioning
confidence: 90%
“…Revisiting the issue of COX2 expression in hamster Leydig cells, this isoenzyme is detected mainly in reproductively active pubertal and adult hamsters with increased circulating concentrations of luteinizing hormone (LH), prolactin (PRL), and androgens (Frungieri et al 2006, Matzkin et al 2009, 2012b. On the other hand, in adult hamsters exposed to a short-day photoperiod and also in prepubertal hamsters, testicular COX2 is barely detected, coinciding with low serum concentrations of LH, PRL, and androgens (Frungieri et al 2006, Matzkin et al 2009, 2012b.…”
Section: R171mentioning
confidence: 99%
See 2 more Smart Citations
“…As LH stimulates testosterone biosynthesis, the increase in testosterone may feed back to induce COX2 expression in Leydig cells. A recent study reported that testosterone induced COX2 expression and prostaglandin F2a production in hamster Leydig cells (Matzkin et al, 2009). These effects of testosterone were abolished by the anti-androgen bicalutamide.…”
Section: Lh-induced Negative Signaling In Star Gene Expressionmentioning
confidence: 99%